Characteristics and Functions of Infection-enhancing Antibodies to the N-terminal Domain of SARS-CoV-2 - Ruth Connor; Mrunal Sakharkar; Garrett Rappazzo; Chengzi Kaku; Nicholas Curtis; Seungmin Shin; Wendy Wieland-Alter; Jordan Wentworth; Daniel Mielcarz; Joshua Weiner; Margaret Ackerman; Laura Walker; et al. (Case Western Reserve University, 2024)
Background: Fcγ-receptor (FcγR)-independent enhancement of SARS-CoV-2 infection mediated by N-terminal domain (NTD)-binding monoclonal antibodies (mAbs) has been observed in vitro, but the functional significance of these antibodies in vivo is less clear.  Methods: We characterized 1,213 SARS-CoV-2 spike (S)-binding mAbs derived from COVID-19 convalescent patients for binding specificity to the SARS-CoV-2 S protein, VH germ-line usage, and affinity maturation. Infection enhancement in a vesicular stomatitis virus (VSV)-SARS-CoV-2 S pseudovirus (PV) assay was characterized in respiratory and intestinal epithelial cell lines, and against SARS-CoV-2 variants of concern (VOC). Proteomic deconvolution of the serum antibody repertoire was used to determine functional attributes of secreted NTD-binding mAbs. Results: We identified 72/1213 (5.9%) mAbs that enhanced SARS-CoV-2 infection in a PV assay. The majority (68%) of these mAbs recognized the NTD, were identified in patients with mild and severe disease, and persisted for at least 5 months post-infection. Infection enhancement by NTD-binding mAbs was not observed in intestinal and respiratory epithelial cell lines and was diminished or lost against SARS-CoV-2 VOC. Proteomic deconvolution of the serum antibody repertoire from 2 of the convalescent patients identified, for the first time, NTD-binding, infection-enhancing mAbs among the circulating immunoglobulins directly isolated from serum. Functional analysis of these mAbs demonstrated robust activation of FcγRIIIa associated with antibody binding to recombinant S proteins.  Conclusions: Functionally active NTD-specific mAbs arise frequently during natural infection and can last as major serum clonotypes during convalescence. These antibodies display functional attributes that include FcγR activation, and may be selected against by mutations in NTD associated with SARS-CoV-2 VOC.